Description Of The Use Heart Medicine Based On Medical Records - Ully Widya Rochmatil Ulla; Hepni; Chici Cahaya Gustin Limbong (International Journal of Health Engineering and Technology, 2023)
Cardiovascular disease (CVD) ranks first as a cause of death in the world, more than any other disease. Cardiovascular disease is a non-communicable disease that most often causes death. Cardiovascular disease is still a global health problem. This type of research was conducted descriptively with a retrospective approach which aims to describe the characteristics of patients and heart disease medications in outpatient BPJS patients at HKBP Balige General Hospital based on medical records for the period January-February 2022. The results showed that by gender, namely in 57% for men and 43% for women. Patient characteristics based on age are 26-35 years 3%, 36-45 years 10%, 46-55 years 27%, 56-65 years 28%, 66 years and over as much as 32%. Characteristics based on the type of drug, namely bisoprolol 26%, Candesartan 15%, Furosemide 13%, Spironolactone 10%, Nitokaf Retard 8%, Amlodipine 6%, Digoxin 6%, atorvastatin 5%, Simarc 5%, Aptor 3%, Simvastatin 2%, and ISDN 1%. Conclusion: There are 12 types of drugs used in medical records, including Amlodipine, Furosemide, Spironolactone, Aptor, Simvastatin, Atorvastatin, Bisoprolol, Nitrokaf retard, ISDN, Candesartan, Digoxin, Simarc.